Plateau pika fecal microbiota transplantation ameliorates inflammatory bowel disease manifestations in a mouse model of colitis - Yang, Yayuan; Cui, Baiqiang; Lv, Yanan; Lu, Xiangnan; Shen, Wenxiang; Feng, Min; Ding, Xuezhi; Dong, Pengcheng; Wang, Yu (Frontiers in Microbiology, 2023)
Inflammatory bowel disease (IBD) is a serious global public health concern. Although the pathogenesis of the disease is currently unknown, it has been reported to be associated with both intestinal microbiota and inflammatory mediators. There is evidence suggesting that the feces of the Plateau pika is useful for treating gastrointestinal injuries and pain. Although fecal microbiota transplantation is highly efficacious intervention for IBD prevention, however, potential the transfer of pathogenic microbes or toxic substances is potentially hazardous. Fortunately, micropore filtering of the donor feces can minimize the risk of bacterial infection allowing retention of the therapeutic effects of the residual bacteriophages. Here, we demonstrated that Plateau pika feces not only alleviated the IBD symptoms but also promoted optimal structure and composition of the intestinal microbiota. Additionally, Plateau pika feces transfer also enhanced phenotypic features, such as, body-weight, disease activity index, and histological scores. In conclusion, Plateau pika feces was found to protect mice against colitis induced by dextran sodium sulfate by reducing inflammation and regulating microbial dysbiosis. These findings suggest the potential of Plateau pika feces as an alternative therapy for IBD.